EFEKTIVITAS Sansevieria trifasciata laurentii MENURUNKAN CEMARAN LOGAM TIMBAL DAN KADMIUM DI TANAH TERCEMAR AIR LINDI - Saleksi, Riki; Yanova, Shally; Irawan, Bambang (Jurnal Tanah dan Sumberdaya Lahan, 2025)
The background of this research is the high level of heavy metal contamination of lead (Pb) and cadmium (Cd) at the former Final Disposal Site (TPA) Talang Gulo, Jambi Province. Preliminary results showed that the concentration of Pb reached 615 mg/kg and Cd was 5.145 mg/kg, exceeding the safe limits set by the Indonesian Ministry of Environment and Forestry Regulation Number 2 of 2023 concerning Soil Quality Standards, which are 300 mg/kg for Pb and 3 mg/kg for Cd. Sansevieria trifasciata laurentii can be used as a phytoremediation agent to address this contamination issue. The objectives of this study were (a) to analyze changes in the concentrations of heavy metals Pb and Cd before and after the phytoremediation process, and (b) to evaluate the effectiveness of Sansevieria trifasciata laurentii in reducing heavy metal concentrations in soil contaminated by landfill leachate at TPA Lama Talang Gulo, Jambi. The results showed that over 8 weeks of observation, Sansevieria trifasciata laurentii effectively reduced the concentrations of Pb and Cd. The plant was able to absorb Pb by 61-91% and Cd by 52-83%. Based on the results of the T-test, a significance value of > 0.05 (0.080) was obtained, with a t_calculated value of 7.867 and a t_table value of 63.1875. Since the t_calculated value was greater than the t_table value, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted, indicating a significant difference in heavy metal reduction before and after phytoremediation. This research confirms that Sansevieria trifasciata laurentii is effective in reducing the concentration of Pb and Cd in the soil at TPA Lama Talang Gulo, Jambi. This plant has the ability to accumulate heavy metals, making it a potential natural solution for remediating contaminated soil.